Assessment of synthetic musks, polychlorinated biphenyls and brominated flame retardants in adipose tissue of obese northern Portuguese women – Metabolic implications - Sousa, Sara (2023)
Obesity is a worldwide multifactorial disease linked to persistent pollutants exposure amongst other factors. Humans are daily exposed to an assort of pollutants, such as polychlorinated biphenyls, brominated flame retardants and synthetic musks. These, also known as endocrine disruptors, were all found in human adipose tissue, the preferable matrix for the assessment of long-time accumulation. There are several accounts of hazardous effects of polychlorinated biphenyls and brominated flame retardants on the human organism, whereas for synthetic musks little is still known. Hence, in this study, the levels of polychlorinated biphenyls, brominated flame retardants, and synthetic musks were measured in samples of adipose tissue from 188 Obese Portuguese Women (subcutaneous or scAT and visceral or vAT). After which, associations between pollutants levels and several biochemical parameters from assorted of metabolic processes were studied. Brominated flame retardants were not found in any sample analysed, synthetic musks were found in all the samples analysed (100 % detection frequency) with median levels of 0.4 ± 0.6 μg/g in scAT and 0.4 ± 0.7 μg/g in vAT and polychlorinated biphenyls were found in the majority of samples (<90 % detection frequency) with median levels of 0.1 ± 0.3 μg/g in both tissues. Median concentrations of synthetic musks and polychlorinated biphenyls were similar between scAT and vAT. In total 315 associations were achieved with pollutants levels in adipose tissue, including 273 Spearman's correlations (146 negative and 127 positive). Additionally, 3 multiple linear regressions were achieved. Synthetic musks behave differently than polychlorinated biphenyls and other well-known persistent pollutants in the human body. Synthetic musks behaviour is yet poorly known and their high levels and detection frequencies enforces the need for more studies about their impact on human health. Understanding how these chemicals alter the metabolism is crucial knowledge and hopefully will contribute to improving the treatment and follow-up of obesity in the female population.